The Relationship Between Anger, Moral Distress, and Self-esteem in Nurses - Tahereh Heidari; Vida Shafipour; Samae Shamshiri; Seyed-Nouraddin Mousavinasab; Yadollah Jannati (Guilan University of Medical Sciences, 2022)
Introduction: Due to stressful work conditions, nurses are constantly exposed to various emotions and stressors such as anger and moral distress that threaten their mental health. On the other hand, self-esteem is one of the personality traits essential for people's mental health and improving their performance. Objective: The present study investigates the relationship between anger, moral distress, and self-esteem in nurses. Materials and Methods: This analytical correlational study was conducted on nurses working in the hospitals affiliated with the non-profit organization of Mazandaran Social Security Insurance from August to November 2018. Two hundred nurses were selected for this study via stratified random sampling. The study data were collected using the Cooper-Smith self-esteem inventory, Hamric moral distress scale, and state-trait anger expression inventory. The collected data were analyzed using the Mann-Whitney and Kruskal-Wallis tests, and path analysis was used for testing the conceptual model. Results: The mean±SD age of the nurses was 36.24±5.37 years. The mean ±SD anger, self-esteem, and moral distress scores were 113.68 ± 15.04, 26.61 ± 3.49, and 65.66 ± 35.88, respectively. The results of the path analysis model suggested an inverse causal relationship between self-esteem and moral distress (P<0.05). This model also indicated a significant inverse relationship between self-esteem and anger (P=0.01). Conclusion: As the results show, the nurses' self-esteem can mitigate the adverse effects of moral distress and anger. These results show the significant psychological interventions in controlling anger and promoting self-esteem and reducing moral distress among nurses.